Infrared webcam-based non-contact measurement of event-related potentials from event-related pupillary responses: An approach focused on mental workload - Sang In Park; Kim Laehyun; Ha, Ji Hyeon; Mun Sungchul (한국CDE학회, 2022)
The event-related potential (ERP) technique is widely used in various fields, but the requirement for sensor attachment limits its application. The aim of this study was to develop an infrared (IR) webcam-based, non-contact system to obtain the amplitudes and latencies of ERP via measurement of event-related pupillary responses (ErPRs) from pupillary rhythms. A total of 32 healthy volunteers participated in this study, and they were required to perform the three levels of mental arithmetic tasks to induce mental workloads (MWLs). ERPs and ErPR were measured by ERP task for the different MWL states and compared based on statistical analysis, classification, correlation, and Bland-Altman plot. Both ERP and ErPR amplitudes and latencies for the three MWL states were revealed by one-way repeated measures analysis of variance to be statistically significantly different. Furthermore, the ERP and ErPR data were found to have 73 and 80% classification performances, respectively, using k-nearest neighbour (10-fold cross validation, n = 96). Correlation coefficients between ERP and ErPR features, which were in the range of 0.642-0.734, indicated good or strong correlation, and good agreement between the indices from these two types of experimental measurement indices was apparent in Bland-Altman plots. An advanced method for IR-webcam-based non-contact determination of ERP components via ErPR measurement was successfully developed, and it was demonstrated that this technique can be used for ERP component monitoring using a low-cost, non-invasive, and easily implemented IR webcam without the burden of sensor attachment.